The effect of interprofessional game-based learning on perceived cognitive load and self-efficacy in interprofessional communication and collaboration in patient safety incidents - Azam Hosseinpour; Fatemeh Keshmiri (PLoS ONE, 2025)
Background This study aims to investigate the effect of the interprofessional game-based learning method on students’ perceived cognitive load and self-efficacy in interprofessional communication and collaboration during patient safety incidents, in comparison to traditional instructional methods. Methods The quasi-experimental study was conducted in 2023–2024. The educational objective was to improve the interprofessional collaboration of the students in patient safety incidents. Students in operating room nursing and anesthesia nursing (n = 60) participated in this study. Interprofessional game-based learning and traditional methods were used in the intervention group and the control group, respectively. Participants completed two questionnaires about cognitive load and self-efficacy two months after intervention. The data were analyzed using descriptive tests (mean, standard deviation, and percentage) and analytical tests (including ANCOVA and Student T-test). Results The IP-GBL intervention significantly improved students’ self-efficacy in the intervention group compared to the control group (F = 26.51, df = 1.57, p-value = 0.0001, Partial Eta Squared = 0.31). The IP-GBL method enhanced GCL and eliminated ECL and ICL compared to the traditional method. (p = 0.0001). Conclusion The IP-GBL enhanced germane cognitive load and decreased the intrinsic and extrinsic cognitive load, which facilitated students’ learning. Patient safety training using interprofessional game-based learning has a favorable educational effect on students’ self-efficacy. The findings indicated that the students’ self-efficacy in interprofessional collaboration and communication regarding patient safety incidents in the surgical department significantly improved. Therefore, the interprofessional game-based learning method in formal and informal education of patient safety that requires collaboration between different professions is recommended.